ANALISIS KONDISI PERMUKAAN JALAN DENGAN MENGGUNAKAN METODE PAVEMENT CONDITION INDEX (PCI) DAN METODE SURFACE DISTRESS INDEX (SDI) - Claudya M. Kusuma; N.A.R.A Mamarimbing; Toar U. Y. Pangkey (Sustainable Construction (SUSCON), 2024)
This research aims to analyze road surface conditions using the Pavement Condition Index (PCI) Method and the Surface Distress Index (SDI) Method. Roads play a vital role in daily mobility and regional development. Good road conditions are a prerequisite for the comfort and safety of road users. However, challenges such as excessive loads, high temperatures, high rainfall and soft soil affect the performance of roads in Indonesia. Road damage can hamper transportation and cause economic losses and accidents. Therefore, road maintenance is necessary to maintain optimal road surface conditions. This study focuses on evaluating road conditions on the Manado-Dimembe section, North Sulawesi, which is an important route with a significant level of damage. The PCI and SDI methods are used to evaluate the type and level of road damage and determine the necessary corrective action. The survey was carried out from STA 0+000 to STA 3+000 to get a comprehensive picture of the condition of the road surface. The results of this research provide important information for planning and developing road networks, as well as providing input into the road technical planning system. With proper maintenance, it is hoped that the condition of the road surface can be maintained to ensure the safety and comfort of road users as well as smooth traffic.